KEVALIDAN DAN KEPRAKTISAN MEDIA SIPEDO (SI PINTAR EKSPLORASI DUNIA PIDATO) BERBASIS ANDROID KODULAR UNTUK PEMBELAJARAN TEKS PIDATO PADA FASE D - Putri, Siska Destiani; Andheska, Harry; Zaitun, Zaitun; Ramadhanti, Dina; Elfitra, Legi; Malik, Abdul; Leoni, Tessa Dwi; Ariance Loren, Fabio Testy (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2025)
This study aims to develop SIPEDO (Si Pintar Eksplorasi Dunia Pidato), an Android-based learning media using Kodular, for teaching speech text material in Phase D at SMP Negeri 12 Tanjungpinang during the 2024/2025 academic year. The development model used is the 4D model (Define, Design, Develop, Disseminate), limited to the development stage. The SIPEDO media is an interactive application that includes features such as learning objectives, learning achievements, content exploration, instructional videos, and interactive quizzes. Validation was conducted by material and media experts, while practicality testing involved 46 students, consisting of 6 in a small group and 40 in a large group. Data collection techniques included interviews, validation questionnaires, and practicality tests. Data were analyzed using both qualitative and quantitative descriptive methods. The validation results showed scores of 85% from the material expert and 97% from the media expert, categorized as very valid. The practicality tests scored 88.6% for the small group and 89.1% for the large group, both categorized as very practical. These results indicate that the SIPEDO learning media is highly feasible for use in Indonesian language instruction, particularly in teaching speech texts at Phase D.